An Investigation On The Supporting And Inhibiting Factors In The Implementation Of Balanced Scorecard As A Performance Measuring Tool At The SSB Primary Taxes Office - Putri, Puspita Widya; Suhendra, Maman (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
Although the balanced scorecard has existed in Indonesia for more than a decade, there exists still relative limited research on how the process, challenges, or results of implementing the balanced scorecard in the public sector, especially at the operational level. This study aims to understand the factors supporting and inhibiting the implementation of the balanced scorecard in the SSB Primary Tax Office (KPP SSB). This study uses a qualitative method with a case study approach. Sources of data come from interviews and the results of literature studies on related documents and regulations. This study found 4 (four) factors supporting success namely officers/employees’ participation, the roles of the superior, communication/cooperation, and facilities and infrastructure. It is also found 5 (five) inhibiting factors for implementing the balanced scorecard namely constraints around the key performance indicator (KPI), not-supportive-yet computer systems/applications, non-KPI assignments, difficulties in finding the replacement of employees, and the existence of joint/shared KPI.